Novel Power Allocation Approach in a Battery Storage Power Station for Aging Minimization - Wang, Shu; Liu, Shuran; Yang, Fan; Bai, Xiaohui; Wang, Shuo; Yue, Chengyan (Frontiers in Energy Research, 2020)
A grid-scale battery energy storage station usually contains multiple battery containers and corresponding electric links. Each link and battery container could become a controllable subsystem when receiving network operators’ orders. Battery containers will perform differently after long-term use, especially considering a mixed utilization of new and recycled batteries. Currently the storage inflow/outflow power is distributed equally among containers. The existing power allocation and control strategy in battery energy storage stations mainly focus on batteries’ capacity constraint, rather than their performance, temperature, and ageing conditions. This paper proposed a novel power allocation approach for multiple battery containers in a battery energy storage station considering batteries’ state of charge, temperature, and potential ageing caused. This method established the mathematical modelling between battery ageing with state of charge, depth of discharge, operating temperature and charging state transition times, thus the potential battery ageing can be accurately calculated. The battery ageing is used as the optimization objective to ensure the total battery ageing occurred in all containers is minimized when executing every power dispatch order. A methodological framework based on a time-sequential simulation is conducted to evaluate the potential benefits and ageing risks of different power allocation strategies. The simulation results showed this novel method helps to balance the ageing, temperature and state of charge between battery containers, leading to a more reliable and secure operation of battery energy storage station.